ANALISIS PERAN PENDIDIKAN AKHLAK DALAM PEMBENTUKAN KARAKTER SANTRI USIA 7-12 TAHUN DI PONDOK PESANTREN AL WASHOYA NGORO JOMBANG - Shefia Febi Arindana; Imam Muslih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Moral education has an important role in developing students’ character students aged 7–12 years old because it is during this period that children's personalities begin to develop. Children begin to learn discipline, responsibility, honesty, manners, and other good habits. Islamic boarding schools (pesantren) are the perfect place to instill these values ​​through the practice of worship, rules, and the role models of educators. This research is intended to identify the role of moral education, the moral values ​​applied, and the supporting and inhibiting factors in the character formation of students at the Al Washoya Kertorejo Islamic Boarding School, Ngoro, Jombang. This study used a qualitative method with a case study type. Data were obtained through observation, interviews, and documentation from the caretakers of the boarding school, the head of the boarding school, the musyrifah (religious leader), Data were analyzed through the stages of data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure validity. The findings of the research show that moral education is implemented through habituation, role models, guidance, and supervision. Moral instillation is carried out through morality towards God, oneself, and fellow creatures. The values ​​developed include honesty, compassion, courage, love, self-control, and cooperation. Supporting factors come from the Islamic boarding school environment, the role models of educators, and parental support, while inhibiting factors stem from the students' emotional state and family background. Moral education is the primary foundation for developing students who are disciplined, independent, responsible, and virtuous.